Fórum comunitário participativo: um estudo de caso no município de icapuí/ce - Silva, Daniel Freitas (2019)
The promotion of social participation is one of the premises of the Federal Constitution (1988) and participatory forums are an important tool that enables social control. In this sense, the present paper presents a case study about the Participative Community Forum - FCP implemented in the city of Icapuí-CE, in order to verify to what extent the FCP actually promotes democratization and enables the participation of the population of Icapuí / CE in the decision making process of the municipal public administration. The case study was adopted as a method, classified as exploratory and qualitative approaches, using bibliographic review, participant observation and the application of questionnaires as techniques. The aim of this work was to verify the implementation of the FCP and its institutionalization process in order to find out what actions are necessary to strengthen it as a state policy. It was found that the FCP is considered as a positive experience for its participants, but that it needs to be improved, mainly as regards its methodology of follow-up of demands, accountability, time of deliberations and periodicity. In this sense, it is proposed the production of internal regulations that regulate the functionality of the Forum, based on the methodology of "meeting in open space" and its legal standardization through a bill, making it a public policy of state that links the current and next managers